Association Between Objective Social Isolation and Unmet Medical Needs: A Nationwide Cross-sectional Study in Korea - Jeong Min Yang; Seul Ki Lee; Jae Hyun Kim (Korean Society for Preventive Medicine, 2024)
Objectives: The aim of this study was to analyze the relationship between objective social isolation (SI) and unmet medical needs (UMN) in adults aged 19 and older. Methods: A cross-sectional analysis was conducted of 208 619 adults aged 19 and older, excluding missing data, using the 2019 Korea Community Health Survey. To analyze the association between objective SI and UMN, the chi-square test and logistic regression analysis were performed. Results: The prevalence of UMN was 1.14 times higher (odds ratio [OR], 1.14; 95% confidence interval [CI], 1.06 to 1.23) among those with SI than among those without SI, and the OR for groups with 5 SI types was 2.77 (95% CI, 1.86 to 4.12) compared to those with no SI types. In addition, a stratified analysis by age group showed that the association between SI and UMN existed even in groups under 64 years old. However, among those aged 65 and older, SI was associated with an OR of 1.53 (95% CI, 1.37 to 1.71) for UMN compared to non-SI. As the number of SI types increased, the prevalence of UMN also increased, indicating a strong association between SI and UMN in older adults. Conclusions: This study found that individuals with SI experienced UMN due to fear and anxiety about interpersonal relationships. Therefore, based on the results of this cross-sectional study, it is necessary to investigate the causal relationship between SI and UMN through future longitudinal data.